Exploratory Factor Analysis with R Software - Abdullah Faruk Kılıç (Anadolu Üniversitesi Eğitim Fakültesi dergisi)
Exploratory Factor Analysis (EFA) is frequently used in educational and social sciences. EFA has been used in scale development and adaptation studies, in particular. Therefore, in this study, how to conduct EFA in R software has been explained. First of all, it is examined whether the data set holds the assumptions of EFA. When examining the assumptions of EFA, a function was written. Then, the number of factors was evaluated via parallel analysis (PA), minimum average partial (MAP), and scree plot. After deciding on the number of factors, EFA was conducted and reported. To report the results, R codes were provided to write the results in a Word document. Five categories and two-factorial data set were used in the current study. Oblimin was used as rotation method. Researchers should edit the R codes in terms of their data set properties.